REPRESENTASI KETIDAKADILAN GENDER DALAM PRAKTIK PERDAGANGAN PEREMPUAN PADA NOVEL MIMI LAN MINTUNA [Representation of Gender Injustice in Women's Trafficking Practices in the Mimi lan Mintuna Novel] - Zahrotun Ulfah (Kantor Bahasa Provinsi Maluku, 2020)
The practice of trafficking in women is still a phenomenon in various countries, including Indonesia. In fact, this problem has been raised into the literary work, Remi Silado's Mimi lan Mintuna. This novel tells the story of Indonesian women who were trafficked to Bangkok for the purpose of sexual exploitation. This study was conducted to reveal the practice of trafficking in women reflected in literary works as the author's response to the social realities that exist in society. This study uses the theory of socialist feminist literary criticism which considers that gender injustice experienced by women is caused by a marriage between patriarchy and capitalism. The method used is descriptive qualitative to understand the phenomenon on the subject of the study and use the assistive method of reading as a woman. Reading as a Woman is the awareness of gender differences in the process of reading literary works that also influence the meaning. The results of this study reveal that the practice of trafficking in women reflected in the novel, there are various gender injustices that are manifested in forms such as making women as objects of violence, sexual objects, economic marginalization, and the formation of stereotypes on women namely as submissive creatures and easily conquered. In response, this study also revealed feminist ideas as a rejection of gender injustice experienced. These feminist ideas include women's liberation from male domination, women who have strength and courage, women's ability to determine their destiny, women who are economically independent, and women who have intelligence. Praktik perdagangan perempuan masih menjadi fenomena di berbagai negara, termasuk Indonesia. Bahkan, masalah tersebut telah diangkat ke dalam karya sastra, Mimi lan Mintuna karya Remy Silado. Novel ini bercerita tentang perempuan-perempuan Indonesia yang diperdagangkan ke Bangkok dengan tujuan ekploitasi seksual. Kajian ini dilakukan untuk mengungkapkan praktik perdagangan perempuan yang tercermin di dalam karya sastra sebagai respons pengarang terhadap realitas sosial yang ada dalam masyarakat. Kajian ini menggunakan teori kritik sastra feminis sosialis yang menganggap bahwa ketidakadilan gender yang dialami perempuan disebabkan oleh perkawinan antara patriarki dan kapitalisme. Metode yang digunakan adalah deskriptif kualitatif untuk memahami fenomena pada subjek kajian serta menggunakan metode bantu yaitu reading as a women.Reading as a Women ialah adanya kesadaran perbedaan jenis kelamin dalam proses pembacaan karya sastra yang turut memengaruhi dalam pemaknaan karya sastra. Hasil kajian ini mengungkap bahwa praktik perdagangan perempuan yang tercermin dalam novel, terdapat berbagai ketidakadilan gender yang termanifestasikan ke dalam bentuk seperti menjadikan perempuan sebagai objek kekerasan, objek seksual, marginalisasi ekonomi, serta pembentukan stereotipe pada perempuan yakni sebagai makhluk penurut dan mudah ditaklukkan. Sebagai responsnya, kajian ini juga mengungkap ide feminis sebagai penolakan atas ketidakadilan gender yang dialami. Ide-ide feminis tersebut, diantaranya pembebasan perempuan terhadap dominasi laki-laki, perempuan yang memiliki kekuatan dan keberanian, kemampuan perempuan dalam menentukan nasibnya, perempuan yang mandiri secara ekonomi, dan perempuan yang memiliki kecerdasan.